Intervention of Autogenic Relaxation on Lowering Pain Scale in Head Injury Patients: A Case Study - Sri Astutik, Wahyu; Nuraida, Noneng; Setiawan, Henri (Alta Dharma Publisher, 2022)
Background : Pain is one of the physiological problems that can be found in mild head injury patients. Efforts that can be made to overcome these problems are autogenic relaxation interventions. Objective: This case study was conducted to describe an autogenic relaxation intervention on lowering pain scale in head injury patients. Method: This study uses a case study design with an evidence-based practice implementation approach that focuses on nursing interventions. The study was conducted at the BLUD RSU Banjar on 25-27 May 2022. The participants in this study were Mr. S aged 35 years, male, complaining of headaches on a scale of 5 (1-10). Pain measurement using Numeric Rating Scale. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data becomes a reference for periodic evaluation of nursing implementation. Results: The patient acknowledged that pain decreased from a 5 to 2 scale after being given an autogenic relaxation intervention. Conclusion: Autogenic relaxation intervention should be suspected to be effective in reducing pain scale in patients with mild head injury, evidenced by the client's subjective acknowledgment that the pain scale decreased from 5 to 2 using the Numeric Rating Scale. Recommendation: This research does not conflict with previous research, so it can be a reference in future research. Clinically, autogenic relaxation intervention can be an alternative intervention to reduce the level of pain scale in patients who experience pain in hospitals and in health centers